Micronutrient deficiencies and the double burden of malnutrition in Vietnamese female adolescents: a national cross-sectional study in 2020Research in context - Xiaomian Tan; Pui Yee Tan; Somphos Vicheth Som; Son Duy Nguyen; Do Thanh Tran; Nga Thuy Tran; Van Khanh Tran; J. Bernadette Moore; Yun Yun Gong (Elsevier, 2024)
Summary: Background: Vietnam is facing a double burden of malnutrition, with increasing prevalence of overweight coexisting with undernutrition (stunting and/or thinness) and micronutrient deficiencies (MNDs). Although malnutrition during female adolescence leads to poor health outcomes with potential intergenerational effects on offspring, no studies have comprehensively investigated MNDs and nutritional status among contemporary Vietnamese female adolescents. Methods: Data from 10- to 18-year-old female participants (n = 1471) in the nationally-representative Vietnam General Nutrition Survey 2020 were analysed. Blood nutritional biomarkers, anthropometric measurements, and sociodemographic data were collected, and associations between nutrition status and MNDs were analysed; with anaemia, iron deficiency (ID), iron deficiency anaemia, low serum zinc, low serum retinol, and any MNDs as specified outcomes. Findings: Prevalence of overweight, stunting, and thinness was 27.2%, 14.3%, and 6.9%, respectively. Low serum zinc was common (39.8%), as was ID (13.4%). Bivariate analyses showed that older age (16-18 years old), ethnic minority status, lower wealth index, and inflammation were associated with MNDs. In adjusted logistic regressions, stunting was associated with increased odds ratio and [95% confidence intervals] of low serum retinol (8.92 [2.26, 35.15], p < 0.01), as was thinness (12.25 [3.47, 43.33], p < 0.01). Stunting was also associated with increased odds of having any MND (2.06 [1.31, 3.25], p < 0.01). Interpretation: More female adolescents were overweight than undernourished in Vietnam in 2020. However, undernutrition, low serum zinc, and ID remain prevalent. Food systems approaches should be considered to stem the stark increase in the double burden of malnutrition in young people living in Vietnam. Funding: UK BBSRC BB/T008989/1.